Pemikiran Tan Malaka tentang Pendidikan, 1920-1926 - Dandy, Dandy (Analisis Sejarah, 2023)
This article aims to dissect Tan Malaka's educational thoughts in Indonesia, focusing on his works published during the period 1920-1926. The research employs a historical methodology, relying on secondary sources in the form of books written by Tan Malaka during his lifetime. Although Tan Malaka was primarily an educator, he was often perceived as a political figure by the general public. Starting from 1920, he published books with the intention of disseminating his ideas globally, established formal schools to educate the children of Indonesia, and sought complete independence for the Republic of Indonesia. In forming formal schools and disseminating his thoughts, Tan Malaka aspired to educate the Indonesian populace, expel the Dutch colonial rule from Indonesia, and attain full sovereignty for the Republic of Indonesia.